Prevalence of substance use and related factors in patients seeking treatment for obesity - Yaluğ, İrem and Özmen, Mine and Tufan, Ali Evren and Yumuk, Volkan (Journal of Dependence, 2005)
Objective: Obese individuals who self present for treatment are commonly found to have associated psychopathology. This study is designed to clarify the prevalence and predictors of substance use in an obese population undergoing treatment in a university hospital. Method: This is a cross sectional study which evaluated 169 patients being followed for treatment of obesity in Istanbul University Cerrahpasa Medical Faculty, Department of Endocrinology, for comorbid psychopathology, by means of structured interviews (SCID I and II). Patients with Body Mass Index (BMI) >25.0 are defined as obese and those with BMI between 25.0-29.9 are divided as stage I, the remainder being stage II. Data were analysed with descriptive statistics, binomial regression analysis and chi square test. A difference at the level of P<0.05 was accepted as statistically significant. Results: The ratios of smoking and alcohol use in BMI Stage I and II groups were 30 % and 10% and 35.8 % and 17.5 % respectively. It did not differ significantly in between groups but was significanlty higher in male patients. Discussion: Our findings clearly indicate that there is a high prevalence of substance use in obese patients, especially for those severely overweight and males. These findings underlie the importance of evaluation for substance use in addition to the medical examination in obese patients.